Relationship Between Physical Exercise and Risk of Depression: An Assessment of Intermediate Variables Through Self-Assessed Health Status and Life Satisfaction in the Chinese Family Tracking Survey (CFPS) Data - Gong C; Li Y; Chen G (Risk Management and Healthcare Policy)
Chaoming Gong,1 Yue Li,2 Gaopeng Chen2 1Xu Hai College, China University of Mining and Technology, Xuzhou, People’s Republic of China; 2School of Physical Education, Huaibei Normal University, Huaibei, People’s Republic of ChinaCorrespondence: Gaopeng Chen, Email hbnucgp@163.comObjective: Depression is a potential health killer. As an important means of preventing various human diseases, physical exercise plays an important role in reducing the risk of depression. Using data from the Chinese Household Tracking Survey, this study analyzed the mechanisms by which physical exercise, self-rated health and life satisfaction reduce the risk of depression.Methods: The data for this study comes from the China Family Panel Studies (CFPS) released by the China Social Science Survey Centre of Peking University. The 2020 survey data was used as the sample, which contained a total of 21,057 individuals. The study variables were analyzed in sequence for reliability and validity, correlation analysis, regression analysis, structural equation model testing, and bias-corrected percentile Bootstrap testing using SPSS 23.0 software and Hayes’ (2013) Process plug-in.Results: Physical exercise was significantly positively correlated with self-assessed health status and satisfaction of life (β = 0.049, p < 0.01; β = 0.075, p < 0.01), and significantly negatively correlated with risk of depression (β = − 0.022, p < 0.01); self-assessed health status was significantly positively correlated with satisfaction of life (β = 0.440, p < 0.01), and significantly negatively correlated with risk of depression (β = − 0.047, p < 0.01); satisfaction of life was significantly negatively correlated with risk of depression (β = − 0.137, p < 0.01).Conclusion: Physical exercise not only negatively predicted the risk of depression, but also indirectly predicted the risk of depression through the independent mediating effects of self-assessed health status and satisfaction of life, as well as chain mediating effects. There were no differences in the effects of physical exercise on depression risk by age, gender and marital status. Significant differences in the effect of physical exercise on depression risk were found among groups with different places of residence.Keywords: physical exercise, risk of depression, self-assessed health status, life satisfaction, CFPS